Identifying The Role of Social media on Real Estate Marketing in Kish Island - Hasan Boudlaie; Foroughi Moghadam , Yahya (Technium Social Sciences Journal, 2021)
Social media marketing has recently been recognized as a vital element of marketing programs and has significantly contributed to their effectiveness. Today Small businesses can, thanks to social media, create sales opportunities comparable to those created by their powerful competitors. Therefore, in the present study attempts are made to identify the impact of social media (Instagram, Telegram, Divar and Sheypour) on marketing in the real estate sector. In the present study, qualitative research method is used to fulfill the objectives of the study. The present study was conducted through a semi-structured interview with 10 real estate agents and property buyers on Kish Island. The results showed that social media can effectively contribute to attraction of customers in the real estate sector and even help customers save time when trying to find their favorite property. The results also showed that Social media can help customers do home search without worrying about the spatial constraints, affect the dissemination of real estate images, affect the relationship between sellers and real estate customers, and finally mitigate the costs of real estate customers.